PENGARUH PENGALAMAN AUDITOR, SUPERVISI DAN INDEPENDENSI TERHADAP KINERJA AUDIT KEUANGAN DAERAH - Ahmad Rifan; Darsono Darsono (Diponegoro Journal of Accounting, 2015)
This research aim to examine the influence of auditors experience, supervision and independence of audit quality financial local government. This research moved from a sense of dissatisfaction with some of the parties, both internal and external, to the quality of the audit of the financial statements of local governments conducted by BPK-RI. The results of this research is expected to contribute to the development of science and its application of accounting in general, especially the implementation of public sector accounting / administration. Especially for the BPK- RI, can be input for improvements that are being or will be implemented in order to improve the quality of audit report.The population of this research is the heads of the general audit team of the local government  financial  statements  of  the  various  offices of  BPK-RI.  The  data  taken  from questionaires  distributed  to respondents.  Independent  Variables  in  this  research  is    auditors experience (X1), supervision (X2) and independence (X3), while the bound variable (dependent) is the quality of audits (Y). Data were analyzed using multiple linear regression analysis (multiple regretion). The results showed that the supervision and independence have a positive and significant impact on audit quality, while the auditors experience  of the variables do not have a significant impact on audit quality.